Separated Parents' Adaptive Responses and States Within Intractable Parental Disputes. Issue 7 (3rd October 2019) - Francia, Leanne; Millear, Prudence; Sharman, Rachael
ABSTRACT: Drawing on interviews with separated parents (N = 40) this Australian qualitative study explored dissonance within intractable parental disputes. The mature defense mechanisms of altruism, suppression, anticipation, and humor emerged as potential adaptive responses to dissonance. The mature defense mechanism of sublimation did not emerge as a potential adaptive response to dissonance within intractable parental disputes. Anxiety was the predominant state reported by separated parents. This study theorized that mature defense mechanisms might partially support the reduction of recurring dissonant states within intractable parental disputes. Those in clinical practice might find it useful to explore defense mechanisms, and the clues they provide, in further understanding and supporting separated parents enmeshed within intractable parental disputes.